Health heat stress in Porto Metropolitan Area : a matter of temperature or (in)adaptation? - Monteiro, Ana (2014)
The aim of this contribution is to understand the negative outcomes for human health during hot weather in a Mediterranean urban environment. Examining seasonal variations of thermal comfort in Porto, by Physiologically Equivalent Temperature (PET), and comparing expected and observed daily mortality (all causes) and morbidity (all causes, respiratory and circulatory diseases), suggests that in southern Europe, people's adaptation techniques for reducing heat stress and associated health risks need to be developed much further. Research already done in Porto shows that social and economic vulnerability must be included alongside with individual characteristics, like age, gender or genetics, when defining the thresholds above which negative health impacts begin to become severe. Findings from Porto show that a climate risk map is needed for every metropolitan area, with sufficient detail to give locally appropriate temperature thresholds taking into account both the local climate and the socio-economic conditions of every sector of the urban environment.